A chaotic pendulum triboelectric-electromagnetic hybridized nanogenerator for wave energy scavenging and self-powered wireless sensing system. (March 2020) - Chen, Xin; Gao, Lingxiao; Chen, Junfei; Lu, Shan; Zhou, Hong; Wang, Tingting; Wang, Aobo; Zhang, Zhifei; Guo, Shifeng; Mu, Xiaojing; Wang, Zhong Lin; Yang, Ya
Abstract: The marine environment monitoring system is of considerable significance to the sea development. However, the power-supply issue of the sensor nodes in the system is a crucial consideration all the time. Here, a chaotic pendulum triboelectric-electromagnetic hybridized nanogenerator integrated with the power management circuit to power the wireless sensing nodes by scavenging wave energy has been proposed. The physical design of the harvester utilized the virtue of low working frequency and high electromechanical conversion efficiency characteristics of the chaotic pendulum. To verify the utility and applicability of the hybridized nanogenerators, several experimental scenarios were selected, the maximum output power of TENG can reach 15.21 μW and the EMG is up to 1.23 mW as triggered by the water wave. The hybridizied nanogenerator can light up about 100 LEDs. Moreover, the self-powered wireless sensing node distant transmission has been realized, and data transmission capability exceeds 300 m. This study provides a new direction of scavenging low-frequency vibrations from the environment of marine, also in the aerospace and industry. Graphical abstract: The chaotic pendulum triboelectric-electromagnetic hybridized nanogenerator has been utilized to scavenge the wave energy for powering the wireless sensing system. The physical design of the hybridized nanogenerator possess the virtue of low working frequency and high electromechanical conversion efficiency characteristics of the chaotic pendulum. This structure provides a new idea of scavenginglow-frequency vibrations from the environment of marine. Image 1 Highlights: A designed chaotic pendulum triboelectric-electromagnetic hybridized nanogenerator is proposed to scavenge the wave energy. This communication provides a new way of harvesting low-frequency vibration from the environment of marine. A chaotic pendulum hybridized nanogenerator possessing the merits of lower working frequency. A low power consumption of power management circuit and wireless sensing node transmission is designed.